Pengaruh Testimoni dan Literasi Ekonomi Syariah Terhadap Keputusan Pembelian pada Fifi Shop di Kabupaten Bone - Iin Asriani; Aksi Hamzah; Hartas Hasbi (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to test the influence of testimonials and sharia economic literacy on purchasing decisions at the Fifi Shop in Bone Regency. Using quantitative methods, data was obtained from 100 respondents through questionnaires which were analyzed using multiple linear regression. The research results show that testimonials have a significant influence on purchasing decisions, where positive testimonials increase consumers' trust and interest. Sharia economic literacy also has a significant influence, showing that understanding sharia principles such as halal products and Islamic financial management influences consumer preferences in purchasing. These two variables influence purchasing decisions significantly when used together. This study provides practical benefits for business actors to use testimonials as a marketing strategy and increase consumer knowledge about sharia economics when promoting sharia-based goods.